Experimental and Numerical Study of Self-Centering Brace with Arc Steel Plate - Mahdi Malek Mohammad Pour; Soheil Monajemi Nejad; AbdolReza Sarvgad Moghadam (Buildings)
Self-centering braces are structural systems that help reduce structural drift when the structure is under the influence of seismic forces. This paper introduces a novel self-centering brace designed to enhance the seismic performance of structures, while also minimizing permanent deflection after an earthquake. The advantages of this brace include easy construction, compatibility with construction practices in Iran, affordability, high capacity for axial force, efficient energy dissipation, adaptability for development, and applicability in various structures. The proposed brace components are presented, and the brace’s behavior under cyclic loading is analyzed. The results highlight the significant impact of arched steel plates on the damping properties of the proposed brace systems. Various parameters, such as thickness, curvature radius, and arched spring width, are considered. Moreover, experimental studies are conducted to explore the behavior of the proposed brace. A comparison between the experimental and numerical modeling results demonstrates the accuracy of the numerical models in relation to the tests.